DDRE-11. SECOND GENERATION IDO INHIBITORS FOR IMPROVING IMMUNOTHERAPEUTIC EFFICACY IN PATIENTS WITH GLIOBLASTOMA. (12th November 2021) - Bollu, Lakshmi; Bommi, Prashant; Wainwright, Derek; Ladomersky, Erik; Zhai, Lijie; Bell, April; Lauing, Kristen
Abstract: INTRODUCTION: Indoleamine 2, 3-dioxygenase 1 (IDO; IDO1) is a rate-limiting enzyme that metabolizes tryptophan and is expressed in >90% of patient-resected glioblastoma (GBM). IDO-mediated tryptophan metabolism has been the proposed mechanism for suppressing the immune response in GBM. Recently, we discovered that IDO also possesses non-enzymic functions that contribute to suppress the anti-GBM immune response. This finding motivated us to develop IDO-Proteolysis Targeting Chimeras (IDO-PROTACs) to degrade IDO protein rather than simply inhibiting IDO enzyme activity. METHODS: Western blot analysis was used to determine IDO-PROTAC efficiency of IDO protein degradation among human and mouse GBM cell lines and PDX. Our lead IDO-PROTAC was tested for toxicity, blood brain barrier penetration, and pharmacokinetics (PK) in wild-type C57BL/6 mice. RESULTS: IDO-PROTACs degrade IDO protein in both tumor and non-tumor cells with a DC50 value of 0.5µM in human GBM tumor cells. Biolayer interferometry (BLI) studies show that IDO-PROTAC forms a binary complex with IDO protein with similar affinity comparable to parental compound – BMS986205. IDO-PROTACs induced IDO ubiquitination and the pretreatment with ubiquitin proteasome inhibitors, MG132 or MLN4924, inhibited IDO protein degradation. In vivo toxicity studies showed that treatment with IDO-PROTAC at 25 mg/kg for 3-weeks did not develop any apparent toxicity in C57BL/6 mice. PK analysis revealed that IDO-PROTAC bioavailabilty reached a peak serum and brain concentration within 30 minutes after intraperitoneal administration. CONCLUSIONS: This study developed a lead IDO-PROTAC compound that efficiently degrades IDO protein in human GBM cells with a moderate bioavailability and blood-brain barrier (BBB) penetration. Future work will focus on the enhancement of BBB penetration, increased bioavailability, and route of administration to improve IDO-PROTAC potency for combination with other forms of immunotherapy for GBM patient treatment.